Self-perceived physical fitness as a moderating variable in the relationship between motor self-efficacy and physical self-concept in school-age physical education students - Galán-Arroyo, Carmen; Mayordomo-Pinilla, Noelia; Castillo-Paredes, Antonio; Rojo-Ramos, Jorge (Frontiers in Psychology, 2024)
The increasing prevalence of mental health disorders has elicited significant concern within society, particularly among adolescents who are disproportionately affected by this concerning trend. Consequently, institutions are seeking efficacious and cost-effective interventions to address this situation, while the scientific community has identified physical activity as a potential means to mitigate this epidemic. Motor self-efficacy and physical self-concept have been demonstrated to confer benefits to the mental health of young individuals, comparable to those of physical fitness. These aspects not only influence physical health but also the emotional and psychological well-being of individuals, contributing to a better overall quality of life. The aim of this study was to analyze the moderating role of self-perceived physical fitness betweenin motor self-efficacy and physical selfconcept, as it could be a moderator between motor self-efficacy and physical self-concept these two variables in high school physical education students. To this end, the Kolmogorov-Smirnov test was applied to identify the non-normality of the data and the Mann-Whitney U test to determine the differences by sex in the variables studied to subsequently perform a moderation analysis and a regression test for the physical self-concept prediction model. The results showed that self-perceived physical fitness positively moderated the relationship between motor self-efficacy and physical selfconcept, enhancing the positive effect size of self-efficacy on physical self-concept. Thus, selfperceived physical fitness is could be important in interventions aimed at improving physical and emotional well-being the quality of life and health of adolescents.